2013
DOI: 10.5713/ajas.2012.12499
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA Diversity and Phylogenetic State of Korean Cattle Breed, Chikso

Abstract: In order to analyze the genetic diversity and phylogenetic status of the Korean Chikso breed, we determined sequences of mtDNA cytochrome b (cyt b) gene and performed phylogenetic analysis using 239 individuals from 5 Chikso populations. Five non-synonymous mutations of a total of 15 polymorphic sites were identified among 239 cyt b coding sequences. Thirteen haplotypes were defined, and haplotype diversity was 0.4709 ranging from 0.2577 to 0.6114. Thirty-five haplotypes (C1–C35) were classified among 9 Asia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Among the two investigated breeds, the compositional frequency of A base was the highest (30.2%) among three other bases (T, 27.2%; C, 26.00%; G, 16.3%). The nucleotide composition in this study was similar to published studies in cattle (Kim et al 2013), sheep (Pakpahan et al 2016;Sofla et al 2017) and chicken (Adamu et al 2016), suggesting that composition of A+T nucleotides in those animals was higher than C+G nucleotides.…”
Section: Sequence Variation and Genetic Diversitysupporting
confidence: 90%
“…Among the two investigated breeds, the compositional frequency of A base was the highest (30.2%) among three other bases (T, 27.2%; C, 26.00%; G, 16.3%). The nucleotide composition in this study was similar to published studies in cattle (Kim et al 2013), sheep (Pakpahan et al 2016;Sofla et al 2017) and chicken (Adamu et al 2016), suggesting that composition of A+T nucleotides in those animals was higher than C+G nucleotides.…”
Section: Sequence Variation and Genetic Diversitysupporting
confidence: 90%
“…Previous studies reported a base composition bias towards A + T in the mtDNA D-loop region (Lei et al, 2006;Yang et al, 2014) and in the cyt b gene (Cai et al, 2007;Kim et al, 2013) in cattle. In fact, earlier research (Perna and Kocher, 1995;Saccone et al, 1999Saccone et al, , 2000 indicated that mitochondrial genomes of many organisms including mammals were guanine and cytosine (GC) poor.…”
Section: Discussionmentioning
confidence: 92%
“…The results of previous studies reported that there were 4 transition substitutions (C>T) in Cyt b gene sequence of swamp buffaloes in Asian mainland (Thailand and Peninsular Malaysia), but transversion substitution was not found (Lau et al, 1998). Also, Kim et al (2013) found fifteen transition substitutions in the Korean cattle from fifteen polymorphic sites identified. In contrast, in the Pakistani river buffaloes (Nili-Ravi, Kundi) there were 79 transition substitutions (g.33A>G and g.46C>T) and 43 transver- Bbc BK BD KL KN TR NTB BTN NAD 1 1 --------1 1.27 2 -9 10 6 2 ----27 34.18 3 -1 -------1 1.27 4 -1 -------1 1.27 5 ---6 4 10 10 5 3 38 48.10…”
Section: Tasj-1924 27mentioning
confidence: 91%
“…The main reason for using mitochondrial DNA marker because the mitochondrial genome has a relatively small size (± 16500 bp), and a rapid evolutionary rate, which causes high intra-species diversity (Avise, 1994). Mammalian mitochondrial DNAs show several special features such as an absence of intron, maternal inheritance, all offsprings from the same female parent having the same mitochondrial DNA sequence, the existence of single copy of orthologous genes, the lack of recombination events and a high mutation rate (Linacre & Tobe, 2011;Kim et al, 2013). Mitochondrial DNAs of the animal contain thirteen protein-coding genes and are considered as strong markers for genetic variation analysis such as at the family, genus, and species levels (Arif & Khan, 2009;Doosti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation